Platelet-derived growth factor (PDGF)-BB regulates the airway tone via activation of MAP2K, thromboxane, actin polymerisation and Ca2+-sensitisation - Annette D. Rieg; Said Suleiman; Carolin Anker; Nina A. Bünting; Eva Verjans; Jan Spillner; Sebastian Kalverkamp; Saskia von Stillfried; Till Braunschweig; Stefan Uhlig; Christian Martin (Respiratory Research, 2022)
Abstract Background PDGFR-inhibition by the tyrosine kinase inhibitor (TKI) nintedanib attenuates the progress of idiopathic pulmonary fibrosis (IPF). However, the effects of PDGF-BB on the airway tone are almost unknown. We studied this issue and the mechanisms beyond, using isolated perfused lungs (IPL) of guinea pigs (GPs) and precision-cut lung slices (PCLS) of GPs and humans. Methods IPL: PDGF-BB was perfused after or without pre-treatment with the TKI imatinib (perfused/nebulised) and its effects on the tidal volume (TV), the dynamic compliance (Cdyn) and the resistance were studied. PCLS (GP): The bronchoconstrictive effects of PDGF-BB and the mechanisms beyond were evaluated. PCLS (human): The bronchoconstrictive effects of PDGF-BB and the bronchorelaxant effects of imatinib were studied. All changes of the airway tone were measured by videomicroscopy and indicated as changes of the initial airway area. Results PCLS (GP/human): PDGF-BB lead to a contraction of airways. IPL: PDGF-BB decreased TV and Cdyn, whereas the resistance did not increase significantly. In both models, inhibition of PDGFR-(β) (imatinib/SU6668) prevented the bronchoconstrictive effect of PDGF-BB. The mechanisms beyond PDGF-BB-induced bronchoconstriction include activation of MAP2K and TP-receptors, actin polymerisation and Ca2+-sensitisation, whereas the increase of Ca2+ itself and the activation of EP1–4-receptors were not of relevance. In addition, imatinib relaxed pre-constricted human airways. Conclusions PDGFR regulates the airway tone. In PCLS from GPs, this regulatory mechanism depends on the β-subunit. Hence, PDGFR-inhibition may not only represent a target to improve chronic airway disease such as IPF, but may also provide acute bronchodilation in asthma. Since asthma therapy uses topical application. This is even more relevant, as nebulisation of imatinib also appears to be effective.